Greek imaginary : from Homer to Heraclitus, seminars 1982-1983 - Castoriadis, Cornelius, 1922-1997 (Edinburgh University Press, 2023)
Offers in English for the first time philosopher Cornelius Castoriadis's earliest surviving lectures on the ancient Greeks Includes renowned scholar Pierre Vidal-Naquet's essay, 'Castoriadis and Ancient Greece'" (1999), which provides an introduction and memorial to Castoriadis's researchIncludes Castoriadis's previously untranslated, substantive essay, "'Political Thought'" (1979), which presages many of the key themes in the seminarsIncludes Castoriadis's thematic reports on his teaching in the 1980-1984 seminarsIncludes an "Editors' Introduction" plus extensive editorial commentary on the seminars and an Analytic Table of Contents provided by the academic editor of the French edition of the volume (from 2004)Includes a "Foreword" by the translator, which highlights key terms in the seminarsThis book collects 12 previously untranslated lectures by Castoriadis from 1982 to 1983. Castoriadis focuses on the interconnection between philosophy and democracy and the way both emerge within a self-critical imaginary already in development in the work of early Greek poets and Presocratic philosophers.Displaying both mastery of the relevant scholarship and original interpretation, he reveals the birth of a society that would place its highest value in calling itself and its institutions into question. He argues that this spirit would develop directly into the twin signatures of the Greek world, namely radical philosophy, on the one hand, and radical democratic practices, on the other. Like no previous interpreter, Castoriadis allows us to feel the existential need, already present in the earliest Greek thinkers, to question the significance of human existence and to share in shaping its meaning. The Greeks not only did this, he argues, they also began the equally important work of establishing the institutions to support such a project."